(3TQM bUjOI GHf GdMGLH aj GdYQhVs - (3efUhQ Hf eMeO Hf eMeO GddROj GdgQhj GdTGaYj, CHh CMeO,J (B440 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ceG jfHZj dLdGdg agPG JYdjb Ydi bUjOI Hf GdMGLH GYde HCf GdYQhV daXG eTJQc ai GUWdGMge Hjf gPG GdYde faSg hHjGf GdLRA GdCNj ef GdfUa GdChd ef HjJ GdTYQ hGdYQhV s
(3BNQgG (B:s
(3hbjGS GdeJbOejf Cf GdJGA hGdcGa GdePchQJjf hGdgGA GdSGcf eG abHdgG gj GdQhi dGefG bHdgG s
(3GdeXfhf CfgG eShOI GdeDdas
(3hHBNQgG YOI ahGFO hJYdjbGJ ai Yde GdYQhVs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B303s
Keywords: (3eJaQbGJs